Biomedical Application of Reactive Oxygen Species–Responsive Nanocarriers in Cancer, Inflammation, and Neurodegenerative Diseases - Liu, Jinggong; Li, Yongjin; Chen, Song; Lin, Yongpeng; Lai, Haoqiang; Chen, Bolai; Chen, Tianfeng (Frontiers in Chemistry, 2020)
Numerous pathological conditions, including cancer, inflammatory diseases, and neurodegenerative diseases are accompanied by overproduction of reactive oxygen species (ROS). This makes ROS vital flagging molecules in disease pathology. ROS-responsive drug delivery platforms have been developed. Nanotechnology has been broadly applied in the field of biomedicine leading to the progress of ROS-responsive nanoparticles. In this review, we focused on the production and physiological/pathophysiological impact of ROS. Particular emphasis is put on the mechanisms and effects of abnormal ROS levels on oxidative stress diseases, including cancer, inflammatory disease, and neurodegenerative diseases. Finally, we summarized the potential biomedical applications of ROS-responsive nanocarriers in these oxidative stress diseases. We provide insights that will help in the designing of new ROS responsive nanocarriers for various applications.